Intelligence Gathering Imperative: A Tool for Successful Security Outfits’ Operation - Enyia, Jacob Otu; Achu, Ayuk A.; Duke, Otu; Njong, Cleverty Afu; Takim, Tiku Oru; Okpa, John Thompson (International Journal of Criminology and Sociology, 2022)
This study examines the recent security challenges Nigerians and non-Nigerians encounters in their daily existence to eke a living. These threats are orchestrated by the activities of one of the deadliest terrorist group in the world (Boko Haram), and herdsmen notorious killers, armed banditry, cow rustling by rustlers, incessant kidnapping especially students in schools and unsuspecting Nigerians and non-Nigerians alike; which has made Nigeria federating states unsafe for any meaningful socio-economic development to thrive. To achieve this, two objectives were stated to include, underscore the overarching relevance of intelligent gathering in preventing crime and understand the elaborateness of intelligence gathering that can be utilized to mitigate crimes outcomes. The study found that intelligence gathering is the disconnect that has precipitated this state of affairs in Nigeria. Equally responsible is the people’s loyalty which is first and foremost skewed to ethnoreligious and political considerations instead of the country. It was recommended among other appeals to include: The National Intelligence Agency (NIA) of Nigeria which is the coordinating security agency should be properly funded and personnel trained in modern intelligence gathering techniques, the unnecessary bickering, in-fighting for superiority between and among security agencies in Nigeria should be discouraged because this itself is a big challenge in security equation of Nigeria; and serious effort should be made to stop the politicization of security intelligence gathering matters based on tribe, ethnic group, religious and political affiliations.